2019
DOI: 10.1007/s12649-019-00737-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Schinus molle Essential Oil Extraction Residues

Abstract: The present study determines the best conditions for the fermentation of Schinus molle drupes by the combination of different types of hydrolysis with the search for an adequate yeast strain. Schinus molle seed residues from an essential oil extraction plant (EOEP) have a high potential for ethanol production. Native yeast strains were isolated from the residues and were used to ferment the lignocellulosic residues, along with baker's yeast (Saccharomyces cerevisiae) at 30 °C and pH 5.5 for comparison. Morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Therefore, we ruled out the hypothesis that fucose would be present in considerable amount in commercial S. molle. Further, Solis et al reported that fresh and residue seeds of S. molle contained 16% glucose; however, they did not confirm fructose and fucose [22]. In our method, we used 70% EtOH for sample extraction, while Feriani et al used hot water extraction for S. molle fruits from Tunisia.…”
Section: Color and Sugar Content Analysismentioning
confidence: 84%
“…Therefore, we ruled out the hypothesis that fucose would be present in considerable amount in commercial S. molle. Further, Solis et al reported that fresh and residue seeds of S. molle contained 16% glucose; however, they did not confirm fructose and fucose [22]. In our method, we used 70% EtOH for sample extraction, while Feriani et al used hot water extraction for S. molle fruits from Tunisia.…”
Section: Color and Sugar Content Analysismentioning
confidence: 84%
“…The physical and chemical pretreatments performed on beet and date materials were required to reduce recalcitrance biomass for hydrolyzing complex sugars (mainly sucrose) into simple intermediate products and increase the reactive surface area [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A comparison of the yield and concentration of ethanol of all fermentation processes is presented in Table 3.…”
Section: Bioethanol Yield and Concentrationmentioning
confidence: 99%
“…Thus, an efficient pretreatment should increase the content of fermentable sugars (glucose, fructose, galactose, etc.) and will results in a good yield of fermentative bioethanol [6,10,11]. Palm date is very rich in sucrose, fructose and glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of drupes of the pirul ( Schinus mole ) tree were ground and subjected to acid hydrolysis obtaining 14 g/L of monosaccharides and to enzymatic hydrolysis obtaining 3.2 g/L of monosaccharides. Finally, fermentation was carried out comparing native yeasts and common yeast Saccharomyces cerevisiae ; with the former, an ethanol concentration between 200 and 250 mg/g was obtained, while with the latter only 125 mg/g (Solis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%